Perceived Job Discrimination in Australia: Its Correlates and Consequences (The Australian Journal of Labour Economics, 2013)
We use data from a nationally representative Australian household panel survey to examine the extent and nature of self-reported job discrimination, its correlates, and its associations with various employment outcomes and measures of subjective wellbeing. We find that approximately 8.5 per cent of job applicants and 7.5 per cent of employees report being discriminated against in the preceding two years, most commonly on the basis of their age. Gender is found to be a common factor predicting perceived discrimination in both job applications and in the course of employment, but the determinants of these two types of discrimination are otherwise somewhat different. In particular, age is a significant determinant of perceived discrimination in job applications only, while being a mother of young children is a significant factor only for discrimination in the course of employment. We also find that, holding other traits constant, ethnic and religious minorities are not significantly more likely to perceive they have been discriminated against. Little evidence of adverse effects of perceived job discrimination is found for wage levels, wage changes and the probability of promotion, but we find large negative effects on subjective outcomes such as job satisfaction and self-assessed probability of job loss.